2017
DOI: 10.1097/ccm.0000000000002533
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline: Safe Medication Use in the ICU

Abstract: This guideline evaluates the ICU environment as a risk for medication-related events and the environmental changes that are possible to improve safe medication use. Prevention strategies for medication-related events are reviewed by medication use process node (prescribing, distribution, administration, monitoring). Detailed considerations to an active surveillance system that includes reporting, identification, and evaluation are discussed. Also, highlighted is the need for future research for safe medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 314 publications
0
50
0
2
Order By: Relevance
“…Apart from some clinical decision support systems, commonly used systems such as computerized prescriber order entry and bar-coded medication administration lack personalized recommendations to optimize medication effectiveness and minimize side effects [ 51 ]. Wang et al [ 47 ] applied a deep learning network based on RL to exploit medication recommendations with a data-driven strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from some clinical decision support systems, commonly used systems such as computerized prescriber order entry and bar-coded medication administration lack personalized recommendations to optimize medication effectiveness and minimize side effects [ 51 ]. Wang et al [ 47 ] applied a deep learning network based on RL to exploit medication recommendations with a data-driven strategy.…”
Section: Resultsmentioning
confidence: 99%
“…A literatura registra que os pacientes internados em UTI estão mais vulneráveis a danos, pois existe a utilização de maior número de fármacos. 16,17 Apurou-se também que houve prescrições que chegaram a ter mais de três MPPs. Esses dados chamam a atenção para a necessidade de se instituírem práticas seguras que funcionem como barreiras para proteger os pacientes.…”
Section: Discussionunclassified
“…Indeed, in many cases, we identified a lack of knowledge in this field leading to errors. Education is recommended as part of any program intending to reduce AEs and MEs 25. Poor communication within the health care team and failures in organization were the second type of frequent issue.…”
Section: Discussionmentioning
confidence: 99%
“…As recommended recently in a large review, prevention strategies for medication-related events have to be applied for each phase within the medication-use process. Active surveillance systems that include reporting, identification, and evaluation were highlighted 25. The same review indicated that there was no evidence on the impact of benchmarking for patient safety–surveillance strategies on the rates of MEs, ADEs, or mortality in critically ill patients 25.…”
Section: Discussionmentioning
confidence: 99%